Metabolic fate of adenine in red blood cells during storage in SAGM solution. Issue 10 (5th August 2016) - Paglia, Giuseppe; Sigurjónsson, Ólafur E.; Bordbar, Aarash; Rolfsson, Óttar; Magnusdottir, Manuela; Palsson, Sirus; Wichuk, Kristine; Gudmundsson, Sveinn; Palsson, Bernhard O.
Abstract : BACKGROUND: Red blood cells (RBCs) are routinely stored and transfused worldwide. Recently, metabolomics have shown that RBCs experience a three‐phase metabolic decay process during storage, resulting in the definition of three distinct metabolic phenotypes, occurring between Days 1 and 10, 11 and 17, and 18 and 46. Here we use metabolomics and stable isotope labeling analysis to study adenine metabolism in RBCs. STUDY DESIGN AND METHODS: A total of 6 units were prepared in SAGM or modified additive solutions (ASs) containing 15 N5 ‐adenine. Three of them were spiked with 15 N5 ‐adenine on Days 10, 14, and 17 during storage. Each unit was sampled 10 times spanning Day 1 to Day 32. At each time point metabolic profiling was performed. RESULTS: We increased adenine concentration in the AS and we pulsed the adenine concentration during storage and found that in both cases the RBCs' main metabolic pathways were not affected. Our data clearly show that RBCs cannot consume adenine after 18 days of storage, even if it is still present in the storage solution. However, increased levels of adenine influenced S ‐adenosylmethionine metabolism. CONCLUSION: In this work, we have studied in detail the metabolic fate of adenine during RBC storage in SAGM. Adenine is one of the main substrates used by RBCs, but the metabolic shift observed during storage is not caused by an absence of adenine later in storage. The rate of adenine consumption strongly correlated with duration of storage but not with the amount of adenine present in the AS.